Pengaruh Sales Promotion dan Word of Mouth Terhadap Purchase Decision Dengan Brand Image Sebagai Variabel Mediasi - Sari, Feny Rahma; Isharina, Ikhtiara Kaideni (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2024)
This study aims to determine the effect of sales promotion and word of mouth on purchase decisions with brand image as a mediating variable in air purifier products in East Java. This type of research is explanatory research. The study used a sample of 120 respondents by distributing questionnaires via Google form. The sampling technique used in this study is judgement sampling based on the characteristics of the respondents, namely respondents who have air purifier products from March 2020 to August 2022, respondents are currently in Malang City and Surabaya, and the respondent is at least 17 years old. Testing the research hypothesis using the Partial Least Square (PLS) based Structural Equation Model (SEM) approach. The results of the study found that sales promotion has a positive influence on brand image, word of mouth has a positive influence on brand image, sales promotion has a positive influence on purchase decisions, word of mouth has a positive influence on purchase decisions, brand image has an influence positive effect on purchase decision, sales promotion had a significant influence on purchase decision through brand image, and word of mouth had a significant influence on purchase decision through brand image of air purifier products during the Covid-19 pandemic in the people of East Java.   Abstrak Penelitian ini ditujukan untuk mengetahui pengaruh sales promotion dan word of mouth terhadap purchase decision dengan brand image sebagai variabel mediasi pada produk air purifier di Jawa Timur. Penelitian menggunakan sampel sebanyak 120 responden dengan pengambilan data menggunakan google form. Teknik sampling yang digunakan dalam penelitian ini adalah purposive sampling berdasarkan karakteristik responden, yaitu responden memiliki produk air purifier dari Bulan Maret tahun 2020 sampai Bulan Agustus 2022, responden sedang berada di Kota Malang dan Surabaya, dan responden Minimal berusia 17 tahun. Pengujian hipotesis penelitian menggunakan pendekatan Structural Equation Model (SEM) berbasis Partial Least Square (PLS). Hasil menunjukkan bahwa ketiga variabel yakni sales promotion, word of mouth dan brand image mempunyai pengaruh positif terhadap purchase decision, sales promotion dan word of mouth mempunyai pengaruh positif terhadap purchase decision melalui mediasi brand image pada produk air purifier selama Pandemi Covid-19 di Jawa Timur.